A Theoretical Study on the Structural, Electronic and Optical Characteristics of Tetraaza Macrocyclic - Nur Halimatus Saadiah Binti Abdullah
Pd (II) complex containing tetraaza macrocyclic ligand has already been an important topic of current research studies, especially in catalysis, waste treatment application, and biomedical. The most unique properties of macrocycles containing nitrogen atoms are high selectivity towards transition metal ions and a high tendency to form macrocyclic compounds. The established method of synthesising tetraaza macrocyclic ligand by introducing a transition metal ion as a templating agent has demonstrated difficulties in the decomplexation process because template ions are too stable. Later, one pot synthesis of the non-template has been introduced resulting in protonated tetraaza macrocyclic ligand and metal complex. However, until today, there are limited theoretical studies that specifically reported on metal-ligand interaction in complexation. Therefore, this study examined the structure of the Pd(II) tetraaza macrocyclic ligand and further explored its electronic properties through density functional theory (DFT) calculation. The molecular geometry shows that the Pd(II) atom successfully fits in the macrocyclic ligand and metal-ligand interaction contributes to the stability of the Pd (II) tetraaza macrocyclic ligand. Then, the optical properties of Pd(II) tetraaza macrocyclic ligand were investigated at excited state using timedependent density functional theory (TD-DFT) in gas medium observed frontier molecular orbitals indicate high electron mobility since only little energy is required for the electron transfer process. The optical responses on Pd (II) tetraaza macrocyclic ligand in hexane, toluene, chloroform, methanol, acetonitrile, and water environment using integral equation formalism of polarizable continuum model (IEF-PCM) show significant changes of the energy gap, absorption peaks, and hyperpolarizability values compared in gas medium.